Cidadania, inclusão e biopolítica : a identidade linguística em contradição no processo seletivo vestibular dos povos indígenas no Paraná - Gonçalves, Raquel Fregadolli Cerqueira Reis (2012)
Language is a reference to nationality and is constitutive of national memory. The institutionalization of Portuguese as the official language of Brazil was never an undebated affair. It was rather the officialization, imposed by political trends, of colonial principles. Since identities are effectively kept by cultural practices, such as language, beliefs, uses and customs, political decisions are unwarrantly introduced. It may be stated that political trends are active agents in the construction of a nation's culture. Consequently, political actions also rule the gaze on the other. The differences among the concepts that define the contemporary Amerindian from the erstwhile one are acknowledged. Predominant and linguistic cultural parameters are still extant as a referential to attribute the Brazilian status to first nation Brazilians. Citizenship is consequently a disposition that organizes and rationalizes the guidelines that attenuate the differences among the subjects when educational opportunities are made possible. Discussion involves the Tenth University Entrance Examination for Amerindians in the State of Paraná, Brazil, according to State Law 13134 of 2001, amended by the 2006 State Law 14995, which permits that Amerindians of indigenous communities compete for admission in the state and federal universities in the state of Paraná, Brazil. Current essay aims at understanding and pinpointing the contradictions within the political, social and linguistic stance in the representation process. Reflections are thus provided on the integration of Amerindians within the university, taking into consideration the concepts on History (discursive) and Memory, and on the linguistic and national identity for the formation of citizenship of indigenous subjects enrolled for the entrance exam. Issues are raised on the contradictions in the linguistic field that involve Amerindians as different and incapable subjects, and thus distancing them from the citizen condition. Essays written within the context of the Tenth University Entrance Examination for Amerindians in the state of Paraná in 2010 are analyzed. Theoretical and methodological reflections are foregrounded on History, Cultural Studies and French Discourse Analysis and their evolution in Brazil. Results show that the inclusion of Brazilian Amerindians within non-Amerindian society may be provided on acknowledging these subjects as citizens. Inclusion is based on normalization procedures that frame the Amerindian within non-Amerindian parameters. Inclusion and preservation are contradictory since the former is maintained by full respect. However, Brazilian national culture, based on colonial values, is based on the tolerance principle. Relationships between Amerindians and non-Amerindians are still conflicting and consolidate themselves within an environment of tension and contradiction.